Rancang Bangun Aeropendulum Twinmotor dengan Kontrol Fuzzy Logic Berbasis Matlab-Simulink dan Arduino - Muhammad Iqbal; Heri Subagiyo; Yusmar Palapa Wijaya; Amirul Huda (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
This paper presents the design and development of a twin-motor aeropendulum (half-quadcopter) system as a control systems learning platform using a fuzzy logic controller (FLC). The system is implemented using a real plant in the form of a half-quadcopter, an IMU MPU6050 sensor combined with a complementary filter for angle estimation, and an integration of Arduino and Matlab-Simulink for controller design and response visualization. Compared to conventional PID controllers, the FLC is selected due to its ability to handle system nonlinearities without requiring an accurate mathematical model. The main contribution of this work lies in the development of a low-cost educational platform that integrates a real plant, a non-contact sensor with improved durability, and real-time system response visualization. Experimental results at a 30° setpoint show a rise time of 0.5 s, a settling time of 5.8 s, a maximum overshoot of 21.3%, and a steady-state error of 0.2%, along with good disturbance rejection capability. These results demonstrate that the proposed system is effective and suitable as an interactive learning platform to enhance students’ understanding of control system concepts.